Nanomotion technology for testing azithromycin susceptibility of Salmonella enterica - Mariliis Hinnu; Toomas Mets; Ivana Kerkez; Marta Putrinš; Niilo Kaldalu; Gino Cathomen; Marta Pla Verge; Danuta Cichocka; Alexander Sturm; Tanel Tenson (Microbiology Spectrum)
ABSTRACT Invasive salmonellosis caused by Salmonella enterica subspecies affects millions of people every year, mostly children from low-income countries, and is associated with a high mortality rate. Azithromycin is used to treat invasive salmonellosis resistant to first-line drugs despite conflicting effective concentrations in vitro and achievable serum concentrations in vivo. As resistance levels to azithromycin are rising, we demonstrate that nanomotion technology, which is based on measuring changes in bacterial nanoscale movements, can be used for rapid phenotypic testing of Salmonella’s susceptibility to azithromycin. Additionally, the use of nanomotion enabled the detection of the bactericidal effect. Nanomotion changes under various culture conditions correlated with susceptibility measured by minimum inhibitory concenctration (MIC) determination, colony-forming unit (CFU) counting, and fluorescent reporter-based estimates of intrabacterial azithromycin accumulation. Environmental conditions, both during azithromycin treatment and throughout the recovery period, significantly affect the antibacterial response to azithromycin. Azithromycin susceptibility in Salmonella is detectable after only 2 h of treatment. This reflects the quick action of the antibiotic, which could be one of the contributing factors behind the clinical efficacy of azithromycin for Salmonella treatment. Our study underscores the critical role of assay conditions, which greatly influenced both azithromycin efficacy and the test results.IMPORTANCEAzithromycin is used as a last-resort antibiotic to treat life-threatening infections caused by Salmonella enterica, a high-priority pathogen according to the World Health Organization. Resistance levels to azithromycin are increasing, highlighting the need for rapid susceptibility testing. In this study, we demonstrate that nanomotion technology can detect azithromycin susceptibility in Salmonella, suggesting its potential use for rapid resistance detection in clinical settings and its future use with azithromycin. Additionally, the study shows that nanomotion technology can be used for susceptibility and postantibiotic effect testing for various pathogens and antibacterials, including those generally regarded as bacteriostatic.